Peripheral ossifying fibroma: A clinical entity in the mandibular incisor region- A case report - Ira Gupta; Swati Mishra; Rohit Gupta; Saranik Sarkar (Wolters Kluwer Medknow Publications, 2021)
Peripheral ossifying fibroma (POF) is one of the inflammatory reactive exophytic nodular growth, commonly occurring on the gingiva. It is seen more often in females, in the interdental papilla and anterior part of the maxilla. It represents unique clinical characteristics and diverse histopathological features. Surgical excision is the treatment of choice but with a reported recurrence rate of 7%-45%. In the present case report, a 15-year-old female patient reported with the chief complaint of painless swelling in the mandibular anterior region. An excisional biopsy was obtained and sent for histopathological diagnosis. On histopathological examination, it was confirmed as POF. The purpose of this article is to present a case of POF and review the current literature on this condition, so that, such condition can be treated through proper diagnosis and treatment planning.